2015
DOI: 10.1177/1043986215607253
|View full text |Cite
|
Sign up to set email alerts
|

Microaggressions, Injustices, and Racial Identity

Abstract: Inspired by the recent theory of African American offending and the lack of race-centered concepts in criminological literature, I aim to answer four general research questions: (a) Do criminal justice injustices impact African Americans differently than other forms of racism? (b) Do different emotional states increase African Americans' likelihood of offending? (c) Does having a positive racial identity buffer against the negative effects of racial discrimination? and (d) Do the effects of racial discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 122 publications
2
4
0
Order By: Relevance
“…Although all of the studies examining racial/ethnic stigma were cross-sectional and thus cannot be used to infer causality, experiencing racial/ethnic stigma was associated with more risk-taking and criminal behaviors across several studies. This is consistent with the theory of African American offending (Isom, 2016; Unnever, 2014), which considers experiencing racial/ethnic discrimination as a significant source of strain that increases anger and depression as well as weakens social ties, which in turn contribute to criminal behavior. Interestingly, several studies also showed that racial/ethnic minorities were not as negatively impacted by criminal involvement stigma when compared to white individuals (Alarid & Vega, 2010; Crawford, White, et al, 2014; Harris, 1976; LeBel, 2012b; K.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although all of the studies examining racial/ethnic stigma were cross-sectional and thus cannot be used to infer causality, experiencing racial/ethnic stigma was associated with more risk-taking and criminal behaviors across several studies. This is consistent with the theory of African American offending (Isom, 2016; Unnever, 2014), which considers experiencing racial/ethnic discrimination as a significant source of strain that increases anger and depression as well as weakens social ties, which in turn contribute to criminal behavior. Interestingly, several studies also showed that racial/ethnic minorities were not as negatively impacted by criminal involvement stigma when compared to white individuals (Alarid & Vega, 2010; Crawford, White, et al, 2014; Harris, 1976; LeBel, 2012b; K.…”
Section: Discussionsupporting
confidence: 89%
“…CAUSES AND CONSEQUENCES OF CRIMINAL STIGMA consistent with the theory of African American offending (Isom, 2016;Unnever, 2014), which considers experiencing racial/ethnic discrimination as a significant source of strain that increases anger and depression as well as weakens social ties, which in turn contribute to criminal behavior. Interestingly, several studies also showed that racial/ethnic minorities were not as negatively impacted by criminal involvement stigma when compared to white individuals (Alarid & Vega, 2010;Crawford, White, et al, 2014;Harris, 1976;LeBel, 2012b;K.…”
Section: The Impact Of Stigma On Criminal Behaviorsupporting
confidence: 64%
“…Counseling and wellness support from school counselors also serves to normalize the feelings that arise surrounding new awareness and insight about race (Rivas-Drake et al, 2014). Through individual or group counseling, counselors can help students foster positive perceptions about their racial group that may buffer against mental health issues and other negative effects of racial discrimination (Choi et al, 2017; Isom, 2016). Building on Bryant-Davis and Moore-Lobban’s (2019) research into utilizing feminist theory for mental health counseling, school counselors can help adolescents of color make sense of their CREID journey by allowing students to explore how structural oppression and racial trauma have affected them.…”
Section: Proposed Model: the Adolescent Cultural Racial And Ethnic Su...mentioning
confidence: 99%
“…Evidence strongly suggests that racial microaggressions are associated with depressive symptoms (e.g., Ajayi & Syed, 2014;R. E. Anderson et al, 2015;Cheah et al, 2020;Isom, 2016;A. N. Miller & Orsillo, 2020;Ramirez & Paz Galupo, 2019).…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…Below, we focus on stress and anxiety, depressive symptoms, general psychological distress and well-being, and physiological functioning. Although beyond the scope of the current review, we acknowledge investigations that have linked racial microaggressions to career indecision and self-efficacy (Bonifacio et al, 2018;Gomez et al, 2011), externalizing behaviors (Dickerson et al, 2019;Isom, 2016;Lui, 2020;Pro et al, 2018;Su et al, 2020), and eating concerns (Le et al, 2020;Longmire-Avital & McQueen, 2019).…”
Section: Documenting the Harmful Effects Of Racial Microaggressionsmentioning
confidence: 99%